The Influence of Financial and Non-Financial Factors on Credit Decisions in The Digital Era For Micro, Small, and Medium Enterprises (MSMEs) in Malang City - Magdalena Opi; Ahmad Mukoffi; Moh. Askiyanto; Adrian Junaidar Handayanto (International Research & Development for Human Beings (IRDH), 2026)
Finding out how financial and non-financial elements affect lending choices in the digital age for MSMEs in Malang City partly and concurrently was the aim of this research. The study that was carried out used quantitative research methodologies. The study sample consisted of 98 respondents, selected through the simple random sampling technique. The researcher used a questionnaire as the method of data collecting. Using the SPSS version 26 software, multiple linear regression was the data analysis technique used. With a t-value of 6.070, the study's findings demonstrated that partly financial elements significantly influenced credit choices, while non-financial factors significantly influenced credit decisions with a t-value of 5.909. The findings also show that, with an F-value of 61.009, or an impact of 56.2%, both financial and non-financial variables significantly influenced lending choices for MSMEs in Malang City in the digital age. The findings of this research make it clear that both financial and non-financial elements are present and contribute significantly to the use of credit.